"No Small Ostentation": Rituals of Collection and Display in Urbanite Trousseaus of the Eighteenth-Century Ottoman Empire - Collaço, Gwendolyn (Muqarnas, 2024)
Between 1730 and 1834, the Ottoman imperial family stopped holding citywide royal marriage ceremonies. During this period, urbanite families beyond the court crafted impressive trousseau processions and in-home displays for their weddings with growing aplomb, garnering admirers among Ottomans and Europeans. Urbanite trousseaus from this era tell a multi-confessional counternarrative that produced spectacles of wealth in the face of intensifying sumptuary legislation from the state and religious canons. This study contextualizes trousseaus as curated collections serving a distinct social function that transcended the immediate utilitarian purpose of its individual parts: the staging of trousseau objects orchestrated strategic moments of artistic appraisal during wedding ceremonies, which aided in gauging the collection’s monetary value alongside the social import of the bride’s family. The migration of the trousseau thus captured a household in motion, revealed to the community’s scrutinizing eyes for the first time. Sources on their construction shed light on the roles of women as collectors, organizers, and, in the case of non-Muslims, corporal embodiments of familial wealth during these material rituals. By combining surviving objects with inventories, legal cases, poetry and narrative accounts, a trousseau’s journey from construction to display became a performative mode of artistic production.